Validity and Reliability of the Agile Leadership Questionnaire Adaption: Indonesian Version - Wijayanti, Brigitta Sonia; Susanto, Hery (LEGAL BRIEF, 2025)
In the competitive advantage of individuals, some abilities need to be owned and have an essential role, such as the ability to lead. One way to develop this ability is through the application of Agile Leadership. Provide evidence of the reliability of the Agile Leadership Questionnaire adaptation with internal consistency between items using Cronbach-Alpha. The validity evidence of the Agile Leadership Questionnaire adaptation consists of content-based validity evidence using the Content Validity Index (CVI), and construct-based validity evidence using Confirmatory Factor Analysis (CFA). CFA evidence indicated a model that did not fit, as did after modification. Exploratory Factor Analysis (EFA) was conducted, and then reliability and validity evidence were re-conducted using the results of EFA. EFA is used to identify the latent structure underlying a set of variables. Reliability evidence uses SPSS 25 software, Confirmatory Factor Analysis (CFA) validity evidence uses JASP 0.15 software. The adaptation research for the Indonesian version of the Agile Leadership Questionnaire with 4 dimensions containing 15 items provides good reliability and construct validity results